Road Offence Information Management System in Nigeria: a Most Needed Technology Intervention - Ndugbu, Leslie Nneji; Ndugbu, Uzoma Kizito (ICSE (Institute of Computer Sciences and Engineering), 2021)
This study is concerned with road traffic offence information management in Nigeria. It focused on trends in road traffic offences information and carried out a critical review of current information and communication and technology compliance state of FRSC with a view to identifying its defects in road traffic offence information management. A system to correct road traffic offence information management failure as identified in the existing system was then proposed. Road traffic offence records and details of current safety measures obtained from FRSC and online in addition to research works, provided the basic data for the study. The system was designed using the object OOAD methodology and implemented using rapid Php IDE on a Windows 7 system, using PHP, HTML,CSS and mySQL technologies and Apache server as the application server. The result showed the high rate of road traffic offence as a result of poor road traffic offence information management and failure to improve on the existing road traffic information management.